Torrefaction of empty fruit bunches under biomass combustion gas atmosphere - Uemura, Y. (Elsevier Ltd, 2017)
Torrefaction of oil palm empty fruit bunches (EFB) under combustion gas atmosphere was conducted in a batch reactor at 473, 523 and 573 K in order to investigate the effect of real combustion gas on torrefaction behavior. The solid mass yield of torrefaction in combustion gas was smaller than that of torrefaction in nitrogen. This may be attributed to the decomposition enhancement effect by oxygen and carbon dioxide in combustion gas. Under combustion gas atmosphere, the solid yield for torrefaction of EFB became smaller as the temperature increased. The representative products of combustion gas torrefaction were carbon dioxide and carbon monoxide (gas phase) and water, phenol and acetic acid (liquid phase). By comparing torrefaction in combustion gas with torrefaction in nitrogen gas, it was found that combustion gas can be utilized as torrefaction gas to save energy and inert gas. © 2017 Elsevier Ltd